Synthesis of P1-(11-phenoxyundecyl)-P2-(2-acetamido-2-deoxy-3-O-α-D-rhamnopyranosyl-α-D-glucopyranosyl) diphosphate and P1-(11-phenoxyundecyl)-P2-(2-acetamido-2-deoxy-3-O-β-D-galactopyranosyl-α-D-galactopyranosyl) diphosphate for the investigation of biosynthesis of O-antigenic polysaccharides in Pseudomonas aeruginosa and Escherichia coli O104. (1st December 2017) - Torgov, Vladimir; Danilov, Leonid; Utkina, Natalia; Veselovsky, Vladimir; Brockhausen, Inka
Abstract: Two new phenoxyundecyl diphosphate sugars were synthesized for the first time: P 1 -(11-phenoxyundecyl)-P 2 - (2-acetamido-2-deoxy-3- O -α-D -rhamnopyranosyl-α-D -glucopyranosyl) diphosphate and P 1 -(11-phenoxyundecyl)-P 2 -(2-acetamido-2-deoxy-3- O -β-D -galactopyranosyl-α-D -galactopyranosyl) diphosphate to study the third step of biosynthesis of the repeating units of O-antigenic polysaccharides in Pseudomonas aeruginosa and E.coli O104 respectively. Graphical abstract: Highlights: Two phenoxyundecyl diphosphate disaccharides were synthesized. The structures were confirmed by NMR and HRESIMS data. Diphosphates 1 and 2 are substrates for P.aeruginosa and E.coli glycosyltransferases.